Multimodal Electronic Skin: Fingerpad‐Inspired Multimodal Electronic Skin for Material Discrimination and Texture Recognition (Adv. Sci. 9/2021) - Lee, Giwon (Adv Sci (Weinh), 2021)
In article number 2002606, Seung Goo Lee, Kilwon Cho, and co‐workers demonstrate a finger padinspired multimodal mechanoelectric sensor for material discrimination and texture recognition. By integrating various electrical working mechanisms of piezoelectric, triboelectric, and piezoresistive, the sensor can identify and distinguish the external stresses from a single stimulus to a combination of multiple stimuli, enabling a potential application of artificial sensory systems for biomimetic prosthesis and robotic skins. [Image: see text]